Hubungan Bauran Pemasaran Pie Susu dengan Keputusan Pembelian Wisatawan Domestik di Kota Denpasar - TAMBUNAN, SARAH IMANUELLA; SUSRUSA, KETUT BUDI; ANGGRENI, IGAA LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Correlation of Milk Pie Marketing Mix on Domestic Tourist Buying Decisions in Denpasar City The purpose of this study was to determine whether the marketing mix which includes product, price, place, and promotion factors have correlation with the buying decisions of domestic tourists in buying milk pies and to find out the most dominant variables considered by domestic tourists in buying milk pies in the of City Denpasar. Product variables (X1), prices (X2), place (X3), and promotions (X) are the independent variables in this study, with the dependent variable namely the buying decision of domestic tourists (Y). The type of research data used is quantitative and qualitative data. Data sources were obtained from the results of interviews and observations in the companies of Pie Susu Asli Enaaak and Pie Susu Special, and by using literature studies of books, notes relating to research and the internet. Data analysis used was the analysis of Rank Spearman correlation using SPSS 23. The marketing mix which includes products, prices, place, and promotions, has a positive influence on the buying decisions of domestic tourists in Denpasar City. Milk pie products are variables that have a dominant influence on purchasing decisions of domestic tourists in Denpasar City. Based on the results of Rank Spearman's correlation analysis, it is suggested to the milk pie companies to pay attention to the distribution channel variables as well as to establish cooperation in the future with Balinese gift shops 4 and courier services. It is also hoped that they improve the promotion variables by utilizing social media to promote milk pie products, and maintain the gift offer to attract domestic tourists.